2017
DOI: 10.4103/1658-354x.197357
|View full text |Cite
|
Sign up to set email alerts
|

Can ultrasound-guided subcostal transverse abdominis plane block be used as sole anesthetic technique?

Abstract: Subcostal transverse abdominis plane (TAP) block anesthetizes area of the abdomen with cutaneous innervation of T6–T10 dermatomes. These abdominal field blocks become very advantageous when cardiac patient presents for noncardiac surgeries as sole anesthetic or as a part of multimodal anesthesia. A 58-year-male came for open surgical repair of subxiphoid incisional hernia developed post coronary artery bypass grafting (CABG). Echocardiography showed hypokinesia of left ventricle (LV) in the left anterior desce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…[4] A case of large incisional epigastric hernia repair in a high-risk cardiac patient (ASA III), which was operated under bilateral subcostal TAP block, was reported by Bihani et al . [9]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] A case of large incisional epigastric hernia repair in a high-risk cardiac patient (ASA III), which was operated under bilateral subcostal TAP block, was reported by Bihani et al . [9]…”
Section: Discussionmentioning
confidence: 99%
“…Although all the study patients were ASA physical status I or II, subcostal TAP block may be particularly advantageous in ASA 3 and 4 by reducing the opioids' requirements. [9] Inability to block visceral component of pain is also a disadvantage of TAP block.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few cases of the use of a TAP block as the sole anesthetic technique have been reported. Recently, TAP blocks have been used as the sole anesthetic technique in inguinal hernia repair [ 5 , 10 ], open gastrostomy [ 3 ], colectomy [ 4 ], ileostomy [ 4 ], wedge resection of cecal cancer [ 4 ], and abdominal wall abscess incision and drainage [ 11 ]. In particular, the last abdominal surgery mentioned above was similar to the present study in the type of surgery and location of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are some differences in the literature, the analgesic effect of TAP blocks is generally found in the T6-L1 dermatomes of the anterolateral abdominal wall [ 1 , 5 , 8 , 12 ]. However, a cadaveric study by Tran et al [ 13 ] demonstrated that TAP blocks most effectively blocked the dermatomes of T11-L1 and only 50% of the T10.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation